2017
DOI: 10.1128/msphere.00140-17
|View full text |Cite
|
Sign up to set email alerts
|

Selectable Markers for Use in Genetic Manipulation of Extensively Drug-Resistant (XDR) Acinetobacter baumannii HUMC1

Abstract: Multidrug-resistant (MDR), extensively drug-resistant (XDR), and pan-drug-resistant (PDR) strains of Acinetobacter baumannii have frequently been characterized. The ability of A. baumannii to develop resistance to antibiotics is a key reason this organism has been difficult to study using genetic and molecular biology approaches. Here we report selectable markers that are not only useful but necessary for the selection of drug-resistant transformants in the setting of drug-resistant backgrounds. Use of these s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
17
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 44 publications
0
17
0
Order By: Relevance
“…Here, we demonstrated that Gm concentrations that cannot be reached in vivo can be used in vitro (up to 200 g/ml) for selection of A. baumannii MDR clinical strains, like ACICU, whose MIC for Gm is 64 g/ml in LB and LA media. Recent studies have shown that other nonclinically relevant antimicrobials, such as tellurite and Zeo, can be used for in vitro selection (39,40). Zeo is not intended for clinical use, though it has already been employed as a selectable marker for XDR A. baumannii strains (40).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Here, we demonstrated that Gm concentrations that cannot be reached in vivo can be used in vitro (up to 200 g/ml) for selection of A. baumannii MDR clinical strains, like ACICU, whose MIC for Gm is 64 g/ml in LB and LA media. Recent studies have shown that other nonclinically relevant antimicrobials, such as tellurite and Zeo, can be used for in vitro selection (39,40). Zeo is not intended for clinical use, though it has already been employed as a selectable marker for XDR A. baumannii strains (40).…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have shown that other nonclinically relevant antimicrobials, such as tellurite and Zeo, can be used for in vitro selection (39,40). Zeo is not intended for clinical use, though it has already been employed as a selectable marker for XDR A. baumannii strains (40). In this study, replacement of the aacC1 cassette of pVRL1 and pVRL2 with the Zeo resistance gene (i.e., ble) led to the generation of pVRL1Z and pVLR2Z, respectively ( Table 1).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, antibiotics/antimicrobials that are not widely used clinically can be utilized for selection purposes, since incidences of resistance against them are likely to be very low due to the lack of selection pressure. Zeocin (Zeo) resistance markers have recently been shown to be useful for selection purposes in MDR clinical isolates of A. baumannii (13,14). Similarly, apramycin (Apr) has also been shown to have promising activity against MDR A. baumannii strains (15).…”
mentioning
confidence: 99%
“…Similarly, apramycin (Apr) has also been shown to have promising activity against MDR A. baumannii strains (15). Although apramycin is used in veterinary medicine, both apramycin and zeocin are antibiotics that are not used in human clinical settings (14,16), and therefore they are less prone to already-acquired resistance due to lack of selective pressure.…”
mentioning
confidence: 99%